THE POSITION OF NONVERBAL BEHAVIOUR IN FOREIGN LANGUAGE TEACHING AND LEARNING IN THE INDONESIAN CONTEXT - Dewi Novita (Guru Membangun, 2010)
Non-verbal behaviour is a significant aspect of communication. However, despite its importance, teachers are more often inclined to use it in language teaching and learning. It is therefore important to view that to appreciate nonverbal communications values and to integrate it into the context of language teachings are not the same. Efforts should be made from both sides, i.e. those who develop theory, methodology, and materials as well as those who apply these into practice in order to promote the best practice of communicative language learning and teaching. It is expected that the issues raised can soon be addressed so that the teaching and learning of foreign languages in Indonesia can make fruitful progress in the near future.